The Understanding in Transition: Fascicles X, XI and VII of Opus postumum - Thomson, Terrence (Con-Textos Kantianos. International Journal of Philosophy, 2019)
This essay investigates the transformation of the faculty of understanding in Kant’s Transition from Metaphysical Foundations of Natural Science to Physics drafts found in Opus postumum. I argue that in fascicles X and XI Kant implicitly reverses the architectonic order of sensibility and understanding. Without an account of this reversal, Kant’s critique of Isaac Newton’s conception of phenomena and the so called Selbstsetzungslehre (doctrine of self-positing) in fascicle VII fall apart. I argue that what is at stake is a challenge Kant makes to his own presuppositions and a challenge to the Kantian philosopher who wishes to stay with a strictly ‘critical’ Kant.
Keywords: faculties; understanding; sensibility; architectonic; natural science; phenomena